Pattern-Specific Loss of Desmoplakin I and II Immunoreactivity in Erythema Multiforme and its Variants: A Possible Aid in Histologic Diagnosis. (February 2020) - Forrester, Vernon J.; Tran, Benjamin; Hein, Stephanie C.; Wick, Mark R.
Abstract : Abstract: Erythema multiforme (EM), Stevens-Johnson syndrome (SJS), and toxic epidermal necrolysis (TEN) comprise a family of mucocutaneous diseases associated with significant morbidity and mortality. Previous studies have confirmed the presence of autoantibodies to desmoplakin (Dp) I and II in patients with EM, SJS, and TEN. Truncated Dp production leads to characteristic changes visible on light microscopy: perinuclear clumping of keratin filaments and dyskeratotic keratinocyte. Based on these observations, the question arises as to whether a loss of Dp immunoreactivity in skin biopsies could serve as a diagnostic marker of EM, SJS, and TEN. This study analyzed Dp immunostaining patterns in 20 patients with EM or SJS/TEN. To assess the specificity of this approach, Dp immunostaining was also performed on specimens from patients with 5 potential histologic mimics of EM, SJS, and TEN. All of the samples from patients with EM, SJS, and TEN demonstrated absent or markedly diminished staining for Dp. A χ 2 test demonstrated a statistically significant difference between the staining patterns in EM, SJS, and TEN and each of the other diagnostic groups that were investigated. This is the first report demonstrating statistically significant specificity of Dp staining patterns in EM/SJS/TEN as compared with other interface dermatitides.